IOT based Industrial Module For SafteyMeasures - Janardhan Reddy, D; Phani Kumar, S (International Journal of Computer Sciences and Engineering, 2025)
This Paper Represents The Design And Implementation Of Intelligent Systems In The Industries For Monitoring The Temperature, Gas And Humidity In The Environment Of Any Type Of Industrial Areas. This Project Can Be Implemented By Using The IOT Module And A Peripheral Interface Controller (PIC) Microcontroller. Here the wireless sensor devices will sense the area’s environment and transmits that information to the cloud AMAZON WEB SERVICES (AWS) to store that information for further analysis and immediately sends an alert to the Industry for the purpose of protecting themselves from unexpected disaster. We can see that stored data in cloud from any place of the world.